PERBEDAAN ANTARA TIGA KONSEP KECERDASAN (IQ,EQ,SQ) DENGAN AKAL MENURUT AL-QUR’AN - Supratman, Supratman; Abdullah, Abdullah (JURNAL ILMU BUDAYA, 2024)
Howard Earl Gardner is an American educational and psychological figure. He is known as the originator of the theory of multiple intelligences, namely; Intelligence Quotient (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ). The concept of intelligence according to psychology is different from the concept of reason in Islamic literature (Al-Qur'an and Hadith). The meaning of reason in the Al-Quran and the Hadith of the Prophet is apart from intelligence, also the ability to learn, the ability to communicate with other people, adapt to the environment, and other abilities in the form of having a connection with the transcendental and spiritual. By tracing the word 'reason' and words related to it mentioned in the hadith, it becomes clear that this word 'reason' is sometimes used about the origin of human knowledge and sometimes about the results of its knowledge, where each knowledge of the two also has different uses.